HUBUNGAN PERILAKU HIDUP SEHAT DENGAN STATUS KESEHATAN PADA MASYARAKAT KELURAHAN UJUNG - Sulistiarini - Sulistiarini (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2018)
Health is a human right and one of the elements of welfare that must be realized. Individual or community health status is the result of interaction over the various factors both internal and external. The four main factors affecting the health status of the community are genetics, the environment such as social communities, economies, local politics and culture, and behaviors including individual lifestyles, as well as the health care facilities. Health status in Semampir District is low. Low health status caused by unhealthy behavior of the community. This research aimed to analyzed the relation between healthy life behavior with health status of the community in RW XIII Kelurahan Ujung, Kecamatan Semampir, Surabaya. This research used descriptive method with Simple Random Sampling technique, 136 respondents was selected as a sample. The independent variables in this research consisted of smoking behavior, physical activity or exercise, fruit and vegetables consumption behavior. The dependent variable is healthy status. The collected data were analyzed using Chi-square analysis, to determine the strong relationship of research subjects. The is a relationship relationship between vegetable consumption, fruit consumption and smoking behavior with health status bythe p value 0,009, 0,006 and 0,001 respectively as a result. Moreover there is no relationship between sports with health status by the result of p value is about 0.243.